2013
DOI: 10.21608/ejabf.2013.2177
|View full text |Cite
|
Sign up to set email alerts
|

The seaweed (green macroalgae), Ulva sp. as bioindicator of metal pollution in the Mediterranean Coast, Alexandria region, Egypt

Abstract: Changes in heavy metals (Fe, Mn, Zn, Cu, Cd and Pb) concentrations in marine seaweed (green alga) Ulva sp. and seawater collected from the the Mediterranean Coast, Alexandria region, Egypt were investigated during monthly samplings from January to December 2012 to assess the spatial and seasonal variation of these elements as well as the pollutional status at this area. Fe had the highest concentration and Cd found the lowest one. There were statistically positive significant correlations among the levels of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Several studies showed that, Ulva rigida accumulates these toxic metals, especially lead, in significant amounts. (Haritonidis & Malea, 1999;Saeed & Moustafa, 2013;Ustunada, Erdugan, Yilmaz, Akgul, & Aysel, 2011). This research also showed that, the sampling station of Ulva rigida was more reliable in terms of lead and cadmium pollution having regard to these low values.…”
Section: Resultssupporting
confidence: 54%
“…Several studies showed that, Ulva rigida accumulates these toxic metals, especially lead, in significant amounts. (Haritonidis & Malea, 1999;Saeed & Moustafa, 2013;Ustunada, Erdugan, Yilmaz, Akgul, & Aysel, 2011). This research also showed that, the sampling station of Ulva rigida was more reliable in terms of lead and cadmium pollution having regard to these low values.…”
Section: Resultssupporting
confidence: 54%